1999
DOI: 10.1042/cs19980185
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum levels of interleukin-6, soluble interleukin-6 receptor and tumour necrosis factor receptors to the acute-phase protein response in advanced pancreatic cancer

Abstract: The level of the acute-phase response is a major predictor of survival in patients with advanced pancreatic cancer. This study examines the association between the acute-phase protein response, as determined by serum C-reactive protein, and serum levels of interleukin-6, soluble interleukin-6 receptor and the soluble tumour necrosis factor receptors in patients with pancreatic cancer. Thirty-four blood samples were collected from 13 patients with advanced pancreatic cancer. Samples were also collected from six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 15 publications
1
32
1
8
Order By: Relevance
“…Our study did not demonstrate any differences in serum cytokine concentrations between cancer patients and controls. Although some studies have shown an association between serum cytokines and APPs (Martignoni et al, 2005) several have failed to demonstrate such a link and determination of serum cytokines remains an unreliable measure of tissue cytokine activity (Falconer et al, 1994;Barber et al, 1999). Moreover, these findings suggest that circulating cytokines may not be the key mediators of the APPR.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not demonstrate any differences in serum cytokine concentrations between cancer patients and controls. Although some studies have shown an association between serum cytokines and APPs (Martignoni et al, 2005) several have failed to demonstrate such a link and determination of serum cytokines remains an unreliable measure of tissue cytokine activity (Falconer et al, 1994;Barber et al, 1999). Moreover, these findings suggest that circulating cytokines may not be the key mediators of the APPR.…”
Section: Discussionmentioning
confidence: 99%
“…The proinflammatory cytokines such as IL-6 may lead to an APR and trigger tissue catabolism. A significant positive association has been found between the level of the APR and serum levels of IL-6 and soluble TNF-␣ receptors 55 and 75 (12). Evidence for a role of IL-6 in the development of cancer cachexia has come mainly from studies using the murine colon-26 adenocarcinoma, where increasing levels of IL-6 correlated with the development of cachexia, and treatment with a neutralizing antibody to IL-6, but not TNF-␣ or interferon (IFN)␥, attenuated the development of weight loss and other key parameters of cachexia (249).…”
Section: Interleukins 1 and 6 And Interferon-␥mentioning
confidence: 95%
“…Interleukin-6 has been implicated as a mediator of growth control in several human neoplasms including multiple myeloma (Hussein et al, 2002), prostatic cancer (Giri et al, 2001) and colonic cancer (Schneider et al, 2000) and elevation of serum IL-6 level have been reported in some cancers such as renal cell carcinoma (Blay et al, 1992), ovarian cancer (Plante et al, 1994), cholangiocarcinoma (Goydos et al, 1998) and pancreatic cancer (Barber et al, 1999). The binding of IL-6 to its receptor induces homodimerisation of gp130, which leads to cross-phosphorylation and activation of the associated JAK2.…”
mentioning
confidence: 99%